2019
DOI: 10.3389/fmicb.2019.01915
|View full text |Cite
|
Sign up to set email alerts
|

Turning a Collagenesis-Inducing Peptide Into a Potent Antibacterial and Antibiofilm Agent Against Multidrug-Resistant Gram-Negative Bacteria

Abstract: Antimicrobial resistance is becoming one the most serious health threats worldwide, as it not only hampers effective treatment of infectious diseases using current antibiotics, but also increases the risks of medical procedures like surgery, transplantation, bone and dental implantation, chemotherapy, or chronic wound management. To date, there are no effective measures to tackle life-threatening nosocomial infections caused by multidrug resistant bacterial species, of which Gram-negative species within the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 59 publications
(72 reference statements)
1
25
0
Order By: Relevance
“…To produce the target IL-peptide conjugate, hereafter termed MeIm-3.1-PP4, the synthetic route shown in Scheme 1 was employed, starting with the synthesis of the alkyne-modified IL, by reacting 1-methylimidazole (MeIm) with propargyl bromide (step i), according to Hu et al [ 15 ]; the structure of the target propargyl-MeIm (Pr-MeIm) was confirmed by proton ( 1 H) and carbon ( 13 C) nuclear magnetic resonance (NMR) and electrospray ionization-ion trap mass spectrometry (ESI-IT MS), as described in detail in the Supplementary Materials (Figures S1–S3) . In parallel, the amino acid sequence of 3.1-PP4 was assembled by solid-phase peptide synthesis (SPPS, steps ii and iii) as previously reported by us [ 12 ]. Cleavage of half of the peptidyl-resin (step iv) afforded the parent peptide 3.1-PP4.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To produce the target IL-peptide conjugate, hereafter termed MeIm-3.1-PP4, the synthetic route shown in Scheme 1 was employed, starting with the synthesis of the alkyne-modified IL, by reacting 1-methylimidazole (MeIm) with propargyl bromide (step i), according to Hu et al [ 15 ]; the structure of the target propargyl-MeIm (Pr-MeIm) was confirmed by proton ( 1 H) and carbon ( 13 C) nuclear magnetic resonance (NMR) and electrospray ionization-ion trap mass spectrometry (ESI-IT MS), as described in detail in the Supplementary Materials (Figures S1–S3) . In parallel, the amino acid sequence of 3.1-PP4 was assembled by solid-phase peptide synthesis (SPPS, steps ii and iii) as previously reported by us [ 12 ]. Cleavage of half of the peptidyl-resin (step iv) afforded the parent peptide 3.1-PP4.…”
Section: Resultsmentioning
confidence: 99%
“…50 in most cases. In face of the excellent antibacterial properties exhibited by the MeIm-3.1-PP4 conjugate, especially against Gram-negative bacteria, we next evaluated its antibiofilm activity using the K. pneumoniae MDR isolate, KP010, since the parent peptide, 3.1-PP4, had previously displayed a more notable effect against this isolate [ 12 ]. This activity was assessed in two different ways: (i) inhibition of biofilm formation, and (ii) effect on a preformed biofilm.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations